Influence of clinical and radiographical features on complete i denture acceptance in elderly (Mustansiria Dental Journal, 2005)
One hundred fort nine edentuolus atients who were included in this studyseeking for a complete denture. Sixty five patients of them were seeking for a denture forthe first time, 45 patients had a history of one set of denture, and 39 patients had a historyof two sets of dentures. All the technical and the laboratory work for construction of thecomplete denture was followed under the supervision of one prosthodontist. Theevaluation of the dentures regarding function, comfort, appearance and generalsatisfaction was done by the patients themselves. The results indicated that patientsacceptability for wearing a new complete denture was increased in those with a histo ofprevious denture .